SIMULAKRA SECOND ACCOUNT INSTAGRAM FOR FKIP UNTIRTA STUDENTS - wendy, Liyola (LP2M Universitas Muslim Nusantara Al Washliyah, 2024)
Students are people who are easily influenced by popular culture. Students in their daily lives are inseparable from the lifestyle that is uploaded and thoroughly documented on their personal Instagram account. The lifestyle that is followed is based on the times, such as consumption in visiting cafes/malls, buying beauty/skincare products that are influenced by advertisements/beauty vloggers, and fashion trends. So that what is bought and done is based on the sign, prestige, luxury or satisfaction that is felt.In examining the existing problems, researchers used qualitative research with a descriptive approach. This research was conducted at FKIP Untirta with subjects namely FKIP Untirta students. Data collection techniques were carried out by observation, interview and documentation methods. From the research that the researchers have done, the results of the study show that students pack their Instagram account with